Geologia, geoquímica e geocronologia do Complexo Correntina e Suite Rio Corrente, Bloco Guanambi-Correntina, Cráton São Francisco - Guilherme Bozelli Pontes (2023)
The Correntina Complex and the Rio Corrente Suite record one of several convergent episodes that led to the stabilization of the lithosphere of the São Francisco Craton in the Paleoproterozoic, preceding the assembly of the Nuna-Columbia supercontinent. In the work area, the Correntina Complex is characterized by a subalkaline metaplutonic unit of mafic-intermediate composition, with intrusions of metavolcanic units of dacitic and rhyolitic composition, and with a metavolcanosedimentary sequence of chemical and siliciclastic nature known as Extreme Formation. The Rio Corrente Suite is characterized by foliated metagranites of a post-collisional nature, represented by a mesocratic metaluminous unit, peraluminous leucogranites and an alkaline felsic unit. The described units can be interpreted based on geochemical models of subduction of magmatic arcs of low metamorphic grade. LILEs and ETRLs enrichments and HFSE depletions indicate dehydration processes of subducting oceanic crust, while high garnet fractionation and HFSE enrichment mark sub lithospheric sources extracted from the melting of oceanic crust. Isotopic data of U-Pb-Hf zircon reveal a crystallization age of 2,183 ± 9 Ma for the meta-alkali-rhyolite of the RG group, with a juvenile isotopic signature (εHf +5.7 to +9.4) and TDMHf between 2.2 and 2.4 Ga. Whole rock geochemistry data on Nd-Sr obtained from a sanukitoid rock of the SAM group shows εNd(t) of +3.05, TDMNd of 2.31 Ga and 86Sr/87Sr(i) of 0.70173. The U-Pb age obtained in zircon from the sanukitoid rock obtained a crystallization age of 2,324 ± 9 Ma, making it the oldest known occurrence present in the basement of the São Francisco Craton. Our results reveal juvenile sources interpreted as a record as to represent the involvement of the subcontinental lithospheric mantle in the evolution of the Riacian continental arc studied.